Del Noce y el tomismo - Delbosco, Ricardo (Sapientia, 2014)
Augusto Del Noce is a well-known scholar for his philosophical research on the twentieth century. Nevertheless, his work has proven to be hard to classify due to his particular methodology as well as his permanent dialog with other philosophical currents. The present study focuses on the relationship between Del Noce’s thought and Thomistic philosophy. It aims at shedding light on the metaphysical assumptions of the author, on the primary foundations of his approach to interpreting history and modernity in general. In doing so, we depart both from those who understand that Del Noce does not distance himself sufficiently from an idealist and immanentist framework as from those that question the soundness of his metaphysical foundations. We claim that the author under study adheres profoundly and consistently to the metaphysics of being and that it does so with explicit reference to Thomistic philosophy. We reconstruct his formation period, his philosophical relationship to Gilson and his idea of Christian philosophy to explore this issue.